2022
DOI: 10.1108/ebhrm-07-2020-0097
|View full text |Cite
|
Sign up to set email alerts
|

Organizational compassion, person-organization fit and discretionary behaviours in non-governmental organizations: a moderated model

Abstract: PurposeThe authors proposed that Organizational Compassion and Person-Organization-Fit dimensions interactively predict Discretionary Behaviours among employees in the Non-Governmental Organization (NGO) sector in Uganda.Design/methodology/approachThe authors employ structural equation modelling to test hypotheses. The research was carried out in two studies; the second one was done six months after the first study. Two samples of respondents were drawn from NGOs operating in West Nile and Kampala regions, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Person‐organization fit refers to the congruence of a person's values, goals, and personality to an organization's characteristics (Chowdhury & Kang, 2022; Kasekende et al., 2022; Rahman et al., 2022). The congruence or fit between a person and an organization could be supplementary or complementary (Chen & Tang, 2022; Sørlie et al., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Person‐organization fit refers to the congruence of a person's values, goals, and personality to an organization's characteristics (Chowdhury & Kang, 2022; Kasekende et al., 2022; Rahman et al., 2022). The congruence or fit between a person and an organization could be supplementary or complementary (Chen & Tang, 2022; Sørlie et al., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The congruence or fit between a person and an organization could be supplementary or complementary (Chen & Tang, 2022; Sørlie et al., 2022). The former fit occurs when both organizations and individuals share identical characteristics in terms of goals and values, while the latter fit occurs when an organization's psychological, physical, and financial resources meet individuals' needs and preferences (Kasekende et al., 2022). Additionally, the supplementary fit is the subjective evaluation of how well individuals' and organizations’ goals and values are identical, while the complementary fit is the objective comparison of the similarities and differences between the person and organization.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous sizable multinational NGOs collaborate with and through partner organizations that take a more localized, grassroots approach. Kasekende et al (2022) found organizations like NGOs are finding success in their endeavors by generating, promoting, and mobilizing support for employees who display discretionary behaviour. Undoubtedly, discretionary behaviours are the foundation for success in the NGO sector, making it critical for contemporary studies to discover these behaviours' constituent parts.…”
Section: Literature Reviewmentioning
confidence: 99%